Efficacy of venoarterial extracorporeal membrane oxygenation with and without intra-aortic balloon pump in adult cardiogenic shock - Wang, Haiwang; Li, Chuanlong; Li, Duo; Chen, Yuansen; Li, Wenli; Liu, Yanqing; Li, Yongnan; Fan, Haojun; Hou, Shike (Frontiers in Cardiovascular Medicine, 2024)
Intra-aortic balloon pump (IABP) is sometimes coupled with Venoarterial extracorporeal membrane oxygenation (VA-ECMO) to treat patients with cardiogenic shock. In this study, we attempted to evaluate the association of the IABP approach on survival and vascular complication rates in adults with cardiogenic shock undergoing VA-ECMO. We performed a systematic search of original studies on VA-ECMO with and without IABP in PubMed, EMBASE, and the Cochrane Library. A total of 42 studies with 8,759 patients were included. The pooled in-hospital deaths of patients on VA-ECMO with and without IABP were 2,962/4,807 (61.61%) versus 2,666/3,952 (67.45%). VA-ECMO with IABP presents lower in-hospital mortality [risk ratio, 0.88; 95% CI, 0.86-0.91; P<0.00001]. In addition, IABP was associated with lower in-hospital mortality of patients with postcardiotomy cardiogenic shock and ischaemic heart disease. (risk ratio, 0.93; 95% CI, 0.87-0.98; P=0.01; risk ratio, 0.85; 95% CI, 0.82-0.89; P<0.00001). There was no significant difference in in-hospital morbidity in neurological, gastrointestinal, limb-related, bleeding, and infection complications between patients on VA-ECMO with and without IABP. In these observational studies, concomitant use of IABP and VA-ECMO in adult patients with cardiogenic shock was associated with reduced in-hospital mortality.